2007
DOI: 10.1021/jf0623743
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Uncertainty Associated with Sample Processing of Oranges and Tomatoes for Pesticide Residue Analysis

Abstract: The homogeneity of analytical samples and the stability of pesticides during the sample processing of oranges and tomatoes were evaluated. The mean concentrations of 14C-labeled chlorpyrifos in analytical portions (subsamples) after processing show that homogeneity is dependent on sample type as well as the processing procedure. The homogeneity of analytical samples of tomatoes processed cryogenically was much better than those processed at ambient temperature. For tomatoes, the minimum analytical portion mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 12 publications
5
36
0
Order By: Relevance
“…The only other spiked analytes observed to yield <85% recoveries were methamidophos, dichlorvos, and chlorothalonil. The former two pesticides are the most volatile analytes, and the third is known to degrade . As also reported in previous comparisons of cryogenic versus room temperature sample processing conditions, Table indicates small losses of the volatile dichlorvos (14% relative difference) and unstable chlorothalonil (21%) during comminution at room temperature.…”
Section: Results and Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The only other spiked analytes observed to yield <85% recoveries were methamidophos, dichlorvos, and chlorothalonil. The former two pesticides are the most volatile analytes, and the third is known to degrade . As also reported in previous comparisons of cryogenic versus room temperature sample processing conditions, Table indicates small losses of the volatile dichlorvos (14% relative difference) and unstable chlorothalonil (21%) during comminution at room temperature.…”
Section: Results and Discussionsupporting
confidence: 69%
“…This bulk sample is then comminuted to generate a representative test sample portion, typically 10–50 g, for analysis. , As a result of resource limitations and sample throughput needs, sample processing in most routine laboratories is conducted at room temperature. However, it has been demonstrated that cryogenic processing using dry ice (solid CO 2 ) or liquid nitrogen often produces more reliable results. For chlorpyrifos in tomato using a specific chopper, Fussell et al. showed that the same degree of analyte variability could be achieved for a 5 g test sample when using dry ice as 110 g at room temperature, whereas for orange, a subsample size of 5 g provided sufficient homogeneity for both sample processing procedures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended that all laboratories should check that the sample processing procedures employed are fit‐for‐purpose. Secondly, and particularly for fruit and vegetable samples, homogenization at room temperature will disrupt plant cells and release enzymes that can rapidly react and/or degrade certain pesticides . Cryogenic sample processing can reduce both heterogeneity and improve pesticide stability and is therefore recommended for such samples.…”
Section: Validation Of Qualitative Methodsmentioning
confidence: 99%
“…Each duplicate food sample was stored by the volunteers using a fridge box previously provided. At the end of the test days, the samples were transported to the laboratory and immediately homogenised in the presence of dry ice (Fussell et al, 2007).…”
Section: Tablementioning
confidence: 99%